G393(P) Reduction in prescription errors in a neonatal intensive care unit: a completed audit cycle. (27th April 2015) - Fordham, T; Green, H; Badeaa, Q; Ibrahim, H; Subhedar, NV
Abstract : Background: Neonates are particularly vulnerable to harm from medication-related errors. Prescription errors are one of the most important sources of potential harm accounting for approximately two-thirds of all medication-related incidents in this population. Aims: To evaluate the impact of a package of interventions designed to improve prescribing practice by doctors and advanced neonatal practitioners (ANNPs) working in a large UK NICU. Methods: We devised an audit tool to capture data relating to the quality of prescribing across a range of neonatal drug and intravenous infusion/parenteral nutrition prescriptions. The accuracy and completeness of prescriptions were assessed against a list of agreed standards. Prescription charts were selected at random, weekly on the same day each week over a seven week period in both audits; a single individual undertook the baseline audit whereas two individuals performed the re-audit. Following the baseline audit a number of interventions were introduced and implemented including modification of prescription charts, specific improvements in education and training and anonymised publication of prescribers' error rates. Prescribing practice was re-assessed one year later after the package of interventions had been embedded into routine practice. Results: 1087 individual prescriptions were reviewed in total. During the initial audit, there were 16 errors in a total 292 prescriptions assessed giving an error rate of 5.5 per 100 prescriptions. In the re-audit, there were a total of 13 errors in 795 prescriptions examined giving an error rate of 1.64 errors per 100 prescriptions (p = 0.003 compared with the baseline audit). All 13 observed errors were deemed relatively minor prescribing errors and none led to any patient harm. Prescribers were not identifiable in 126 prescriptions (16%). Conclusions: Prescribing errors in neonatal practice are relatively common but rarely result in patient harm. Using a completed audit cycle, we have shown a reduction in prescribing error rates following the implementation of a range of interventions that combined to improve prescribing practice of junior doctors and ANNPs.